Prevalence of asymptomatic malaria and anaemia among elderly population in Osun state Southwestern, Nigeria - Egbewale, Bolaji E.; Akindele, Akeem A.; Adedokun, Samuel A.; Oyekale, Olusola A. (International Journal Of Community Medicine And Public Health, 2018)
Background: Malaria has remained a global burden for many centuries. It remains a major public health disease particularly in the tropic despite several interventional efforts targeted at its elimination. Malaria if not treated early enough could result in patients becoming anaemic. In Nigeria, elderly (60 years and above) represent a vulnerable group of individuals, they enjoy very little attention in terms of specific health related interventions and facilities. This study aimed to assess the prevalence and proportion of asymptomatic malaria infections and anaemia among the geriatric population in Osun state, Southwestern Nigeria. Methods: A community-based cross-sectional study was conducted among 396 elderly with average age of 69.14±7.27 years. Blood samples were collected for the preparation of Giemsa stained blood films for the detection and quantification of malaria parasites microscopically. Packed cell volume (PCV) was assessed using hematocrit. Results: Malaria parasites were present in the peripheral blood of 16.2% of the population and only 9.3% of the elderly were found to be anaemic. The ‘Very old’ age group of >85 years years had highest prevalence of malaria (33.3%) but this was not statistically significant (p=0.17). Male respondents (24.4%) were more infected than females (13.7%) and this was found statistically significant (p=0.015). Having malaria parasite and living in the rural areas were significantly associated with being anaemic, p<0.05 in each case. Conclusions: Considerable proportion of asymptomatic elderly individuals with parasitaemia were found anaemic. This group also represents a silent reservoir for malaria transmission in the country, if not addressed.